Design and analysis of hardware Trojans in approximate circuits. Issue 5 (15th December 2021) - Dou, Yuqin; Wang, Chenghua; Gu, Chongyan; O'Neill, Máire; Liu, Weiqiang
Abstract: Approximate computing can accept errors in computation systems to achieve better utilisation of hardware resources. Approximate computing has been successfully developed in integrated circuits, such as approximate arithemtic circuits and approximate accelerators. Unfortunately, recent works show that approximate circuits also have security vulnerabilities. Hardware Trojan is one of the biggest threats to hardware security. However, very limited research has been conducted on hardware Trojans in approximate circuits. In this letter, two types of hardware Trojans, namely Function‐destructive Trojans and Information‐leaking Trojans, are presented. The Trojans are designed based on the characteristics of approximate circuits. The effectiveness of the hardware Trojans are analysed using the evaluation metrics for approximate circuits.